Use Of Calcium Hydroxide Between Visits In Endodontic Treatment - Silva, Warley Oliveira; Gonçalves, Hugo Rodrigues; Rodrigues, Renata Costa Val (Seven Editora, 2023)
The aim of this study was to conduct a literature review on the effectiveness of endodontic treatment with calcium hydroxide between visits in intracanal medication in teeth with periradicular lesions. The methodology was descriptive, based on PUBMED databases, in English articles published in the last ten years. It was found that the treatment with calcium hydroxide as intracanal medication presents as advantages the improvement of the microbiological state of the root canal system, decreasing levels of bacteria, pro-inflammatory cytokines (PICs) and matrix metalloproteinases (MMPs), standing out as an effective anti-endotoxin agent, being also able to minimize the intensity or severity of postoperative pain after endodontic treatment. It was concluded that the use of calcium hydroxide as an intracanal medication is indicated for multi-visit endodontic treatment in teeth with periradicular lesions prior to definitive root canal obturation. However, the evidence available in the literature is considered insufficient, thus highlighting the need for further studies comparing the long-term success of the treatment. DOI: https://doi.org/10.56238/colleinternhealthscienv1-102